Integração do eclipse com WindowBuilder Pro como solução para o desenvolvimento de sistemas desktop - Santos, Claudir Pereira dos (2011)
This paper deals with the use of frameworks for developing Java Desktop. As theoretical basis, it was referred issues related to productivity in systems development, development of production techniques, metrics to monitor progress and aspects of some tools that can be used. Data collection began running an application to create the database that lets you work visually and then replicate the changes to the generation of database. During entities, also collected data related to the agility to create the drawing of windows the same. Na system and linking through bindings, we analyzed the facility to design, component and linking of aid to work with code. Then shown how to create a report for Java and add it to the main project. Finally, it was shown how to generate a Java executable file to be distributed to end users. As an aid in the exposure data, was used to screen clipping and copy the code source. Next step was to analyze the data where there was the positive impact of the use of frameworks. In the end the results were discussed with the study and present the final considerations.